The relationship between salesperson competencies and performance in the Korean pharmaceutical industry - Seong-kook Kim; Ji-sook Hong (Management Revue, 2005)
This study investigates how competencies lead to performance. We propose that salespersons in the Korean pharmaceutical industry require three central competency dimensions: motive and traits, self-concept, and knowledge and skills. Further, we argue that the level of salesperson competencies is positively related to his/her performance, and that the quality of leader-member exchange positively moderates the relationship between competencies and performance. Results based on analyses of data from a sample of 457 salespersons and managers from 5 different pharmaceutical companies in Korea support our research model.
Keywords: 650; competency; salesperson competency; performance; pharmaceutical industry; leader-member exchange; Korean company; Verkaufspersonal; Kompetenz; Qualifikation; Pharmazeutische Industrie; Südkorea